2014
DOI: 10.1002/mabi.201400179
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Flow Through Immunoassay for CRP Determination Based on Polyethylene Filters Modified withω-Aminocellulose Carbamate

Abstract: A novel method for antibody immobilization is discussed and applied in a column based flow through immunoassay system (ABICAP). It is shown that porous polyethylene material can be modified with different ω-aminocellulose carbamates yielding an amino group containing biocompatible support for antibody immobilization. Anti-h CRP antibodies can be bound covalently to the surface via various homobifunctional cross-linkers. The antibody modified filters are validated for the CRP determination in a sandwich ABICAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Thus, the CRP determination could be performed by a very sensitive rapid flow through immunoassay, which shows a detection limit of 5 ng CRP/ml and a detection range of 5–250 ng CRP/ml. Depending on the ω ‐aminocellulose carbamate and the coupling structure, covalent antibody immobilization could be developed and optimized …”
Section: Applicationsmentioning
confidence: 99%
“…Thus, the CRP determination could be performed by a very sensitive rapid flow through immunoassay, which shows a detection limit of 5 ng CRP/ml and a detection range of 5–250 ng CRP/ml. Depending on the ω ‐aminocellulose carbamate and the coupling structure, covalent antibody immobilization could be developed and optimized …”
Section: Applicationsmentioning
confidence: 99%
“…Dialysis of the dissolved polymers in DMA against water resulted in nanoparticles, their hydrodynamic diameters, zeta potentials and PDI decreasing with increasing hydrophobicity. Functionalized cellulose based materials as biocompatible supports allow a covalent antibody conjugation with high yields and antibody activity . Preliminary studies indicate that the fluorescent nanoparticles can act as a label for biomolecules in bioassays.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was found that ω‐aminoethylcellulose carbamate obtained by the conversion of cellulose phenyl carbonate forms thin films for functional surfaces from aqueous solutions on various substrates like gold and polyethylene (PE) depending on the pH value . Based on this observation, a method for immobilization of antibodies on ω‐aminoethylcellulose‐modified PE was developed . In the present study, the synthesis of ω‐aminoethylcellulose carbamate with low DS and of mixed ω‐aminoethyl‐ p ‐aminobenzylcellulose carbamate is discussed.…”
Section: Introductionmentioning
confidence: 94%
“…[ 19 ] Based on this observation, a method for immobilization of antibodies on ω-aminoethylcellulose-modifi ed PE was developed. [ 20 ] In the present study, the synthesis of ω-aminoethylcellulose carbamate with low DS and of mixed ω-aminoethylpaminobenzylcellulose carbamate is discussed. These novel cellulose derivatives were investigated due to their biocompatibility and cytotoxicity against human HaCaT keratinocytes and antimicrobial activity in vitro.…”
mentioning
confidence: 98%